Process evaluation outcomes from a global child obesity prevention intervention - Pettigrew, Simone; Borys, J.; Ruault du Plessis, H.; Walter, L.; Huang, T.; Levi, J.; Vinck, J. (BioMed Central Ltd, 2014)
Background: While it is acknowledged that child obesity interventions should cover multiple ecological levels (downstream, midstream and upstream) to maximize their effectiveness, there is a lack of evaluation data to guide the development and implementation of such efforts. To commence addressing this knowledge gap, the present study provides process evaluation data relating to the experiences of groups implementing the EPODE approach to child obesity prevention in various locations around the world. The aim of this exploratory study was to investigate the barriers and facilitators to program implementation in program sites around the world to assist in developing strategies to enhance program outcomes. Methods: An online survey that included open-ended questions was distributed to the 25 EPODE programs in operation at the time of the survey (May 2012). The survey items asked respondents to comment on those aspects of program implementation that they found challenging and to suggest areas for future improvement. Eighteen programs representing 14 countries responded to the request to participate in the survey, yielding a 72% response rate. The responses were analyzed via the constant comparative method using NVivo qualitative data analysis software.Results: The main concerns of the various EPODE programs were their ability to secure ongoing funding and their access to evidence-based intervention methods and policy advice relating to relationships with third parties. These issues were in turn impacted by other factors, including (i) access to user-friendly information relating to the range of intervention strategies available and appropriate evaluation measures; (ii) assistance with building and maintaining stakeholder relationships; and (iii) assurance of the quality, independence, and transparency of policies and practices. Conclusions: The findings are facilitating the ongoing refinement of the EPODE approach. In particular, standardized and tailored information packages are being made available to advise program members of (i) the various evaluation methods and tools at their disposal and (ii) methods of acquiring private partner support. Overall, the study results relating to the types of issues encountered by program members are likely to be useful in guiding the future design and implementation of multi-level initiatives seeking to address other complex and intractable health-related problems.